The Role of Water Use Efficiency and Drip Irrigation Technology on Horticultural Crop Production Resilience in Bandung Regency - Farida Arinie Soelistianto; Rully Fildansyah; Tera Lesmana (Westscience Press, 2026)
This study explores the role of water use efficiency and drip irrigation technology in enhancing the resilience of horticultural crop production in Bandung Regency, Indonesia. A quantitative approach was adopted, surveying 85 farmers using a Likert scale to assess their perceptions of water use efficiency, drip irrigation adoption, and its impact on crop resilience. The data were analyzed using SPSS version 25, employing descriptive statistics, correlation analysis, and multiple regression analysis. The findings reveal that water use efficiency and drip irrigation adoption significantly contribute to improved crop resilience, with drip irrigation having a stronger influence. Despite the benefits, cost remains a significant barrier to adoption. The study underscores the importance of promoting drip irrigation to optimize water use, enhance agricultural productivity, and help farmers adapt to climate variability. Recommendations include reducing installation costs and increasing technical support for farmers.